Employee Participation Rights During Company Restructuring: Lessons Learned from the “Capability for Voice” in British Law - Dibra, Migen (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2021)
In the current economic context, marked by a growing number of company restructuring processes as well as a rising unemployment rate, it seems important to address the employee’s issue of job security as well as the need to reduce the negative impacts that some restructuring processes have on businesses and employees. One solution in this regard is to ensure that employees are heard during the restructuring process. Since the Quebec and the federal Canadian legal frameworks on the subject offer insufficient protections, the author’s goal is to find solutions in order to strengthen the existing frameworks as well as to suggest different ways of adopting other legal information and consultation procedures applicable to company restructuring in general. To this end, the author is interested in whether a process of information and consultation of employees in restructuring matters, similar to what exists in the European Union, is possible in Canada, in light of the British experience. In fact, the United Kingdom’s case is particularly interesting for Canada, because this country originally applied a collective laissez-faire approach to employee participation rights during company restructuring which was similar to the North American one. It was only because of mandatory directives of the European Union on the subject that the United Kingdom has set up information and consultation procedures recognized by law. In order to perform this study, we have used the method of comparative law and as a theoretical framework we have applied the capability for voice, developed by Amartya Sen, which provides a method for assessing the impact and relevance of Parliament acts that recognize extended participation rights to employees in regard to a company’s economic decisions. In doing so, we assess the extent that the British statutory instruments, related to the subject matter under study, meet the conditions of the capability for voice, which are prerequisites to pass from the involvement stage of the employees in company decisions to their real influence on such issues.